THE DISTRIBUTION AND ACCUMULATION OF SELENIUM IN ROOTS AND SHOOTS OF PLANTS NATURALLY GROWN IN THE SOILS OF KEBAN'S PB-ZN-F MINING AREA, TURKEY - Sasmaz, Ahmet (Taylor & Francis Inc, 2009)
The objective of this study is to determine the distribution factors and enrichment coefficients between soil and plant parts by studying the accumulation and distribution of selenium (Se) in the roots and shoots of different plants. The plants (9 samples of Euphorbia macroclada, 5 samples of Verbascum cheiranthifolium, 8 samples of Astragalus gummifer) and their associated soil samples were collected from the Keban mining area. The roots and the shoots of these plants, together with the associated soils, were analyzed by ICP-MS. The mean Se value of the contaminated surface soils was found to be two to five times higher than those of previously studied uncontaminated surface soils. Se concentrations of the plant parts were lower than those in their associated alkaline soils, where the plants were grown, except for in the shoots of A. gummifer. Mean Se concentrations in the roots of E. macroclada, V. cheiranthifolium, and A. gummifer were 0.82, 0.22, and 0.47 mg kg(-1) on a dry weight basis, respectively, while Se concentrations were 0.29, 0.26, and 2.66 mg kg(-1) in the shoots on a dry weight basis, respectively. The enrichment coefficients and the distribution factors of those plants were lower than 1, except for the distribution factors of V. cheiranthifolium and A. gummifer plants. Thus, it appeared that the shoots of these plants could make them efficient bioaccumulator plants for Se because of high distribution factors and enrichment coefficients. Due to such factors, they can also be used to clean or rehabilitate soils and areas contaminated with Se.
Keywords: Selenium uptake; Euphorbia; Verbascum; Astragalus; enrichment coefficient; distribution factor